RANCANGAN TEKNIS SISTEM PENYALIRAN TAMBANG PADA PENAMBANGAN BATUGAMPING DI UP. PARNO, DESA KARANGASEM, KECAMATAN PONJONG, KABUPATEN GUNUNGKIDUL, DAERAH ISTIMEWA YOGYAKARTA - Raditya Mahardhika; Hartono; Inmarlinianto (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2022)
UP. Parno is a limestone mining company operating in Karangasem Village, Ponjong District, Gunungkidul Regency. UP. Parno has an IUP with an area of 5.7 hectares by implementing an open mining system (surface mining) with the quarry method. Surface mining affects the surface due to climate. When it rains, the falling rainwater can pool in the mining area and around the lower mining openings. If it is dry, no rainwater enters the mining area. Thus, an adequate mine drainage system design is needed. Water discharge is the main thing to determine a good mine drainage system design. Based on the results of the calculation of rainfall data from 2011 to 2020, it is known that the planned rainfall is 101.70 mm/day, and the rainfall intensity is 43.77 mm/hour with a five-year return period of rain. The purpose of making an open channel is to drain rainwater that enters the mining area and drain runoff so that the mine road does not stagnate. The designed open channel has dimensions of b = 1.50 m; B = 1.00 m; d = 0.60 m; h = 0.50 m; a = 0.60 m. Culverts function to drain water from open channels that cut off haul roads. The culverts required are made of smooth cement surface, with a diameter of 0.35 m. The water flowing by the open channel will go to the settling pond to be purified first before flowing into the river around the mining area. The settling pond is designed to consist of three compartments with an area of 264 m2 each and 666 m3 volume. Dredging of sediment in settling ponds must be carried out every 10 months and 13 days.